(untitled) (Nigerian Journal of Technology, 2018)
In engineering design there is the necessity to carry out biometry of an ailment on sufferers as a pedestal for development of a device that manages the ailment. In this paper, we have carried out the biometry of pain in patients of knee osteoarthritis (OA). The study evaluates causes of knee pain, its severity and effects on daily activities, psychosocial life and sleep. The study population was drawn from five government hospitals in Lagos State. After initial treatment, only patients with knee pain were enlisted as subjects in the study. A standardized questionnaire was used for data collection to determine the causes of the pain, its severity and effects on the operational performance of individuals with OA. Chi-square analysis was carried out on our samples at a statistical level of significance of ? = 0.05. Out of 525 questionnaires that were distributed, 431 (82.10%) were responded to. The outcomes of this study indicate that OA affects individuals of all ages and genders irrespective of their topographical locations. 242 (89.67%) women and 189 (88.97%) men were affected with higher incidence recorded within the age groups of (41-50) and (61-70) with frequency values of 62 (84.00%) and 85 (92.85%) respectively. The risk factors include overweight, occupational hazard and previous history of knee injury. Overweight 132 (91.86%), Obesity 59 (92.28%) and Extreme Obesity 5 (90.37%). Previous injury 173 (90.52) % and non-previous injury is 258 (87.78%). This work studies biometrics of OA as basis for developing a therapeutic management of knee OA, and this is to improve the patient’s pain tolerance and relief of swollen knee without adverse effect. http://dx.doi.org/10.4314/njt.v37i3.40